(Re) Solving Repair After Myocardial Infarction - Leoni, Giovanna; Soehnlein, Oliver (Frontiers in Pharmacology, 2018)
Cardiovascular diseases, including myocardial infarction and its complications such as heart failure, are the leading cause of death worldwide. To date, basic and translational research becomes necessary to unravel the mechanisms of cardiac repair post myocardial infarction. The local inflammatory tissue response after acute myocardial infarction determines the subsequent healing process. The diversity of leukocytes such as neutrophils, macrophages and lymphocytes contribute to the clearance of dead cells while activating reparative pathways necessary for myocardial healing. Cardiomyocyte death triggers wall thinning, ventricular dilatation, and fibrosis that can cause left ventricular dysfunction and heart failure. The ultimate goal of cardiac repair is to regenerate functionally viable myocardium after myocardial infarction to prevent cardiac death. Current therapies for heart failure after myocardial infarction are limited and non-curative. At the moment in clinic, conventional surgical interventions such as coronary artery bypass graft or percutaneous coronary interventions are only able to partially restore heart function, with a minor improvement in the left ventricular ejection fraction. The goal of this review is to provide an overview of endogenous myocardial repair mechanisms possibly transferable to future treatment strategies. Among the innovative factors identified as essential in cardiac healing, we highlight specialized pro-resolving mediators as the emerging factors that provide the key molecular signals for the activation of the reparative cells in the myocardium.